Semipermeable Cellulose Beads Allow Selective and Continuous Release of Small Extracellular Vesicles (sEV) From Encapsulated Cells - Zavala, Gabriela; Ramos, María-Paz; Figueroa-Valdés, Aliosha I.; Cisternas, Pablo; Wyneken, Ursula; Hernández, Macarena; Toa, Pauline; Salmons, Brian; Dangerfield, John; Gunzburg, Walter H.; Khoury, Maroun (Frontiers in Pharmacology, 2020)
The clinical benefit of Mesenchymal Stem Cells (MSCs) therapies is attributable to their pleiotropic effect over cells and tissues, mainly through their secretome. This paracrine effect is mediated by secreted growth factors and extracellular vesicles (EV) including small EV (sEV). sEV are extra-cellular, membrane encompassed vesicles of 40-150 nm diameter that can trigger and signal many cellular responses depending on their cargo protein and nucleic acid repertoire. sEV are purified from cell culture conditioned media using several kits and protocols available that can be tedious and time-consuming, involving sequences of ultracentrifugations and density gradient separations, making their production a major challenge under Good Manufacturing Practices (GMP) conditions. We have developed a method to efficiently enrich cell culture media with high concentration of sEV by encapsulating cells in semipermeable cellulose beads that allows selectively the release of small particles while offering a 3D culture condition. This method is based on the pore size of the capsules, allowing the release of particles of ≤ 150 nm including sEV. As a proof-of-principle, MSCs were encapsulated and their sEV release rate (sEV-Cap) was monitored throughout the culture and compared to exosome isolated from 2D seeded cells (sEV-2D) by repetitive ultracentrifugation cycles or a commercial kit. The isolated sEV expressed CD63, CD9 and CD81 as confirmed by flow cytometry analysis. Under transmission electron microscopy (TEM), they displayed the similar rounded morphology in comparison with sEV-2D. Their corresponding diameter size was validated by Nanoparticle tracking analysis (NTA) Interestingly, sEV-Cap retained the expected biological activities of MSCs including a pro-angiogenic effect over endothelial cells, neuritic outgrowth stimulation in hippocampal neurons and immunosuppression of T cells in vitro. Here, we successfully present a novel, cost and time-saving method to generate sEV from encapsulated MSCs. Future applications include using encapsulated cells as a retrievable delivery device that can interact with the host niche by releasing active agents in vivo, including sEV, growth factors, hormones and small molecules while avoiding cell clearance, and the negative side-effect of releasing undesired components including apoptotic bodies. Finally, particles produced following the encapsulation protocol display beneficial features for their use as drug-loaded delivery vehicles.